School Dropouts and Conditional Cash Transfers: Evidence from a Randomized Controlled Trial in Rural China's Junior High Schools - Di Mo; Hongmei Yi; Linxiu Zhang; Renfu Luo; Scott Rozelle; Carl Brinton (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
Recent anecdotal reports suggest that dropout rates may be higher and actually increasing over time in poor rural areas. There are many reasons not to be surprised that there is a dropout problem, given the fact that China has a high level of poverty among the rural population, a highly competitive education system and rapidly increasing wages for unskilled workers. The overall goal of this study is to examine if there is a dropout problem in rural China and to explore the effectiveness that a Conditional Cash Transfer (CCT) program could have on dropouts (and mechanism by which the CCT might affect drop outs). To meet this objective, we conducted a randomized controlled trial (RCT) of a CCT using a sample of 300 junior high school students in a nationally-designated poor county in Northwest China. Using our data, we found that the annual dropout rate in the study county was high, about 7.0%. We find, however, that a CCT program reduces drop outs by 60%; the dropout rate is 13.3% in the control group and 5.3 % in the treatment group. The program is most effective in the case of girls, younger students and the poorest perfirming students.
Keywords: 330